Internalisasi Nilai-Nilai Etika Bisnis Islam Dalam Perspektif Kompilasi Hukum Ekonomi Syariah - Naily El Muna (INAIFAS Press, 2020)
The development of Islamic banking has experienced significant growth. A survey by the financial services authority (OJK) stated that the assets of the Islamic banking industry increased 14 times from Rp. 21.5 trillion in 2005 to Rp. 296, 2 trillion in 2015. Islamic Banking I should implement the values ​​of Islamic Business Ethics (EBI) according to the compilation of Islamic economic law called KHES. These values ​​are divine values, balance (justice), freedom and responsibility. Furthermore, research is needed on EBI Internalization for Islamic Banking Employees with a Focus on Problems; (1) How is the process of internalizing EBI values? (2) How is the process of internalizing the EBI value from the KHES perspective? Researchers used a qualitative approach to normative juridical case studies. The findings and theories were developed using snowball sampling, which is the process of searching for data from and according to needs. Data collection was carried out by: interviews, observation, and documentation. Data analysis used: data reduction, data presentation, drawing conclusions. The results of this study include: (1) EBI Internalization Process: (a) As a spirit, (b) The existence of emotional ties, equality of managers and users of customer funds, (c) The principle of the object is halal, mutual acceptance, needs, habits, and existential, ( d) Being accounted for in a balanced manner in the form of scope of work, (2) The internalization process for employee EBI in accordance with KHES and Law no. 21 of 2008. Perkembangan Perbankan Syariah mengalami pertumbuhan signifikan. Survey otoritas jasa keuangan (OJK) menyebutkan, aset industri perbankan syariah meningkat 14 kali dari Rp. 21,5 triliun tahun 2005 menjadi Rp. 296, 2 triliun tahun 2015. Perbankan Syariah sayogyanya melaksanakan nilai-nilai Etika Bisnis Islam (EBI) sesuai kompilasi hukum ekonomi syariah disebut KHES. Nilai tersebut yaitu nilai ketuhanan, keseimbangan (keadilan), kebebasan dan tanggung jawab. Selanjutnya diperlukan penelitian Internalisasi EBI Pada Pegawai Perbankan Syariah dengan Fokus Masalah; (1) Bagaimana proses internalisasi nilai EBI? (2) Bagaimana proses internalisasi nilai EBI perspektif KHES?. Peneliti menggunakan pendekatan kualitatif studi kasus yuridis normatif. Temuan dan teori dibangun dengan snowball sampling, yaitu proses pencarian data dari dan disesuaikan kebutuhan. Pengumpulan data dilaksanakan dengan: Wawancara, observasi, dan dokumentasi. Analisis data digunakan: reduksi data, penyajian data, penarikan kesimpulan. Hasil penelitian ini meliputi: (1) Proses Internalisasi EBI: (a) Sebagai ruh, (b) Adanya ikatan emosional, kesederajatan pengelola, dan pengguna dana nasabah, (c) Prinsip objeknya halal saling ridho, kebutuhan, kebiasaan, dan eksistensial, (d) Dipertanggungjawabkan seimbang dalam bentuk ruang lingkup pekerjaan, (2) Proses Internalisasi EBI pegawai sesuai dengan KHES dan UU No. 21 tahun 2008.